Vilas Militares: Parnamirim, o ninho da Força Aérea Brasileira no Rio Grande do Norte - Chaves, Danilo Ferreira (2020)
Parnamirim, since the beggining of its population, has a close relationship with the aviation, becoming, since the 1940‟s, an important location of the Brazilian Air Force (FAB). This research aims to comprehend how the military elements, especially the villages and its residents, relate to the town of Parnamirim, trying to unerstand beyond the territorial impact. Documental and bibliography researches were performed; land use mapping – reaching a radius of 500 meter distance of each village, identifying their surroundings –, and a field research with a questionnaire, utilizing the “bola de neve” (snowball) methodology, with residents of the four military villages of Parnamirim. The research demonstrated that three of the four villages of Parnamirim are insert in privileged locations, surrounded by various commercial and service provider establishments. The privilege of the location can be demonstrated through the perception of its own residents, who affirm reside in a place that provides a variety of services and commerce. It was demonstrated that the economic activities of the city are impacted by the permanence of the military and its families, because every village requires supermarkets, restaurants, drugstores, clothing stores and services such as the town‟s schools and gyms. However, what concerns the military population, it was identified that it chooses to utilize the collective use equipment inside the villages, accessed only by the residents. Because, over time, the military villages in Parnamirim were shaped like closed neighborhoods, restricting the access from local population.